Green manure cover effects on restoration success in Southeast Atlantic Forest biome - Fagoto, Joyce Meireles [UNESP]; Massi, Klecia Gili [UNESP]; Collard, Fabiano Haddad (Ipef-inst Pesquisas Estudos Florestais, 2022)
Active restoration techniques, such as direct sowing, is an important strategy to benefit forest structure formation and to inhibit the exotic grasses invasion, which is an impediment to many restoration projects. The use of green manure in sowing can improve soil cover conditions and inhibit grasses. Thus, in this study we aimed to investigate the role of green manure canopy on invasive grass species??? cover and on growing of native species seedlings in direct sowing sites in the Southeast Atlantic Forest biome. We hypothesized that green manure would suppress the cover of exotic grasses and would benefit native species??? seedling growth. The study monitored six plots of 25 m x 4 m in a restored area (by direct sowing in pits) belonging to the Atlantic Forest biome, located in Cruzeiro municipality, in February 2021, June 2021 and January 2022. Measurements of individuals were the circumference at breast height and the plant height. We also inventoried per pit: canopy diameter, canopy cover and invasive grass cover. We found that a higher green manure canopy cover (regarding plant size and canopy) was responsible for decreasing invasive grass species cover, namely Brachiaria species. In addition, some species had higher canopy cover that suppressed invasive grasses more efficiently. We did not find a positive effect of green manure on native species seedling growth. However, the change from dry season to wet season in canopy cover, together with invasive grasses presence, negatively affected the growth of native species seedlings. These results provide important guidelines and indicate the role of the direct sowing technique for decreasing exotic grasses invasion and the establishment of native species.
Keywords: Permanent preservation area; Ecological restoration; Direct seeding; Native species